The transmission of intangible values in vernacular architecture: The case of the Valencian barraca - Rosaleny-Gamon, Marcel·lí; Eixerés-Ros, Josep (EAAE Annual Conference Proceedings, 2025)
In recent years, the study of vernacular architecture has gained relevance among some professionals in the field of architecture. These professionals have understood the importance of the lessons in environmental, sociocultural and economic responsibility that this type of architecture offers. They believe that recovering past ways of life and construction techniques could be key to addressing the challenges that future generations will face. These lessons are generally based on basic survival principles and, above all, on the rational exploitation of available resources in a specific region. Additionally, there is a desire, or even a need, for the communities inhabiting these territories to be self-sufficient and autonomous. This is due to the limitations imposed by ways of life with lower technological development, which unintentionally lead to a more responsible and sustainable community. These attitudes, which result in certain ways of building, are fundamentally based on the intangible values of these vernacular communities. Thus, in a discipline with such a close relationship to the material, the recovery of these intangible values could be essential when it comes to developing new ways of building or living in a certain region and thereby addressing the global changes we already face every day.